Insights into the black box of collective efforts for the registration of Geographical Indications. (30th November 2016) - Quiñones-Ruiz, Xiomara F.; Penker, Marianne; Belletti, Giovanni; Marescotti, Andrea; Scaramuzzi, Silvia; Barzini, Elisa; Pircher, Magdalena; Leitgeb, Friedrich; Samper-Gartner, Luis F.
Highlights: First comparison of collective efforts for registering Geographical Indications. Five cases in the EU and Colombia show considerable, albeit diverging time efforts. Robust pre-existing producer organisations lower registration efforts. Institutions, number and heterogeneity of actors play a key role. Participatory processes result in benefits relevant for the future GI use. Abstract: Registered Geographical Indications (GIs) communicate to consumers the reputation and quality characteristics of food products linked to the geographical origin. Therefore, farmers and processors consider the protection of GIs as Intellectual Property Rights as a tool for product differentiation and a solution for reducing misuse or free-riding. However GI-registration requires collective action and considerable efforts borne by multiple actors. According to the diverse GI-legal schemes, such as the EU framework, farmers and processors have to agree on the delimitation of the geographical area, production techniques and product quality characteristics contained in the Product Specification. Our paper enters for the first time into the black box of the GI-registration processes by analysing five Protected Geographical Indications in Colombia, Italy and Austria. Cases were selected among products registered according to the EU legislation (EC Regulations 2081/92, 510/2006 and 1151/2012) to represent supply chains of different length (e.g. short and long) and complexity (e.g. number of producers involved). We aim to identify the most critical and (time) demanding phases during the GI-registration processes and the type of private and public actors involved (e.g., farmers, processors, local public authorities, research staff) as well as to quantify their (collective) efforts and degree of involvement (e.g., consultation/co-decision vs. informing about decisions on behalf of others) and to analyse the outcome of the higher or lower involvement of actors. Cross-case comparisons are guided by the Institutional Analysis and Development Framework and the empirical transaction cost analysis. Results show that collective efforts borne by producers and related GI-stakeholders and the resulting collective outcomes are affected by institutional frameworks, group size and heterogeneity as well as ex-ante organisational robustness. Well-established pre-existing producer organisations and the support of local public authorities are critical factors along the GI-registration process. Participatory processes, even if time consuming, may result in a co-learning process as GI-stakeholders can attain better awareness of the product specificities and develop collective strategies and initiatives that should go far beyond the mere GI-registration. This article also adds to the still very small body of the empirical transaction costs analysis. Insights about advantages and efforts of farmers and processors who aim to link terroir and taste of place are not only relevant for the governance of origin food, but also for other rural development processes.